The Need for Large-Scale, Longitudinal Empirical Studies in Middle Level Education Research - Steven B. Mertens; Micki M. Caskey; Nancy Flowers (Middle Grades Review, 2016)
This essay describes and discusses the ongoing need for large-scale, longitudinal, empirical research studies focused on middle grades education. After a statement of the problem and concerns, the essay describes several prior middle grades efforts and research studies. Recommendations for future research efforts to inform policy decisions are provided, including roles for the Middle Level Education Research Special Interest Group (MLER SIG) of the American Educational Research Association (AERA) and other national organizations.
Keywords: middle grades research; longitudinal research; policy implications